Criminalization of the Transmission of the Coronavirus COVID-19 and Its Impact on the Right to a Healthy Environment - AL-KHAWAJAH, Noor; ALKHSEILAT, Abdullah; AL-BILLEH, Tareq; MANASRA, Majd; ALWERIKAT, Naji (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022DO - 10.14505/jemt.v13.7(63).08, 2022)
Murder usually causes death. Unconventional kinds of attacks on human life include the propagation of Coronavirus illness (COVID-19). According to the World Health Organization and medical specialists, COVID-19 is a lethal virus and a poisonous chemical, making its transmission a murderous act. Therefore, it is possible to have several criminal forms related to the transmission of COVID-19 to others. These forms vary according to the consequences resulting from the transmission of COVID-19, so the consequences may be death, which is expected due to this virus; if the victim cannot resist it, the consequences may most often cause harm to others. In addition, these criminal forms vary based on whether the mental element is purposeful or involuntary.